Predicting Customer Churn in Telecom Sector based on Penalization Techniques and Ensemble Machine Learning - Mahdi Naser, Asia; al-shamery, Eman (International Journal of Engineering and Technology, 2018)
Customer Churn Prediction model (CCP)aims to detect customers with a high propensity to leave. The target of this research is to handle a large scale Telecommunication Company and identify potential churn. In the proposed research, Predictive Mean Matching (PMM) algorithm used to handle missing values, instead of removing features or observations with high missing data.First Ensemble Machine learning classifieris offered to investigate and compare the combining of an Ensemble learner based on Generalized Linear Model (GLM) and the prediction values based on tree model using a Random Forest classifier. The suggested CCP model employed the Weighted Accuracy and Diversity (WAD) as an algorithm to find the optimal weights for the proposed Ensemble classifier.The second Ensemble learner based on the generalized linear model is incorporated of penalized methods (Ridge, Lasso,and ElasticNet) with a Logistic Regression method on the binomial family. Randomly generate values between [0, 1] became the weights for this classifier. The Weights are selected according to the principle that weights of highervalue are assigned for great performance classifier to ensure the highestaccuracy of Churn Prediction model. 10-fold, based on five times repeated Cross-Validation (CV) performance technique used to enable efficient and automatic search for the optimal value of lambda Î» parameter for penalization methods.The two Ensemble classifiers incorporated within a customer churn prediction model to handle a large scale dataset, time-dependent features label, and an imbalance data distribution in the Telecommunication industry.Experimental results show an increasein predictive performance. In addition, the results depicted that using of ensemble learning has brought a significant improvement for individual base learners in terms of performance indicators such as Area under Curve (AUC), sensitivity, specificity, Accuracy, and Mean Square Error(MSE), Accuracy is the best candidates for churn prediction tasks.Â Â